1978
DOI: 10.1001/jama.1978.03280490046021
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Folliculitis Acquired From a Health Spa Whirlpool

Abstract: \s=b\Three cases of an unusual Pseudomonas skin infection acquired from a health spa whirlpool were reported, and an epidemiologic survey showed 17 additional cases. This dermatosis is characterized by the abrupt onset of urticarial papules and superficial and deep papulopustules that spare only the head and neck and occur eight to 48 hours after using the whirlpool. Cultures from one patient's pustules and from the spa whirlpool environment were positive for P aeruginosa, serotype 0-11. The condition cleared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
2
11
0
1
Order By: Relevance
“…This is also supported by an earlier observation that superhydration of the stratum corneum favors colonization of skin with P. aeruiginlos(l (19). Occlusion promotes Pseiu-do0msonls infection (35). The rash is most severe in areas occluded by a snug bathing suit (4,12,13,30,43,44), and women wearing one-piece bathing suits are at increased risk (20a), and swimsuits worn for several hours after exposure may facilitate infection (14), but interestingly, this syndrome has also been reported in persons who did not have any clothes on while in the whirlpool (8, 43).…”
supporting
confidence: 73%
See 3 more Smart Citations
“…This is also supported by an earlier observation that superhydration of the stratum corneum favors colonization of skin with P. aeruiginlos(l (19). Occlusion promotes Pseiu-do0msonls infection (35). The rash is most severe in areas occluded by a snug bathing suit (4,12,13,30,43,44), and women wearing one-piece bathing suits are at increased risk (20a), and swimsuits worn for several hours after exposure may facilitate infection (14), but interestingly, this syndrome has also been reported in persons who did not have any clothes on while in the whirlpool (8, 43).…”
supporting
confidence: 73%
“…This is one of an increasing number of outbreaks of Pseludoinonis folliculitis associated with the use of whirlpools. Factors contributing to the occurrence of this syndrome include the high temperature of the water, water turbulence and aeration, heavy bather load per volume of water, the ubiquitous distribution of P. aeruiginosa, and the ability of this organism to withstand chlorine and to multiply rapidly in water at elevated temperatures (16,27,35,43,44). In the outbreak reported here the whirlpool had an automatic disinfectant dispenser.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…P. aerugino8a has been isolated more frequently in hospital swimming pools than in other pools (Schindler, 1978). Outbreaks of infections due to P. aeruginiosa in swimming pools (Reid & Porter, 1981) and health spa whirlpools (Sansker et al 1978) are still being reported. When P. aeruginosa was isolated during this study, large numbers were found in the filter.…”
Section: Discussionmentioning
confidence: 99%